STUDI PEMANFAATAN SOSIAL MEDIA SEBAGAI MEDIA PROMOSI - Mercy Anggina; Siti Filzah; Fifades Ibrani; Jufriyanus Bulolo (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the significant role of social media—such as Instagram, Facebook, and TikTok—as a digital marketing tool that is now starting to replace traditional promotional methods. Using a descriptive qualitative approach through case studies, this research examines how the form and strategy of promotional content on various digital platforms can influence brand awareness and drive sales growth. The results show that social media is highly effective as a promotional tool because it can reach a wider audience, quickly, and at a relatively low cost compared to conventional methods. Furthermore, the interactive features available on these platforms enable two-way communication between businesses and consumers, thus creating stronger and more responsive relationships. These findings emphasize that the success of digital marketing depends heavily on a company's ability to design an engaging, informative, and consistent content strategy, accompanied by a quick response to consumer needs and feedback. Thus, utilizing social media can be an effective approach to strengthening a brand's position and increasing consumer trust and adherence to the products or services offered.